Isolated bilateral congenital lacrimal gland agenesis – Report of two cases - Alwohaib, Manar; Schellini, Silvana Artioli [UNESP]; Elkhamary, Sahar M.; Al Shaikh, Osama (Wolters Kluwer, 2017)
Congenital lacrimal gland agenesis, also called congenital alacrima, is a rare cause of dry eye and is characterized by aplasia or hypoplasia of lacrimal glands. We present two 5-year old children with congenital lacrimal gland agenesis. The two cases had the final diagnosis of isolated bilateral congenital lacrimal gland agenesis and we document the clinical aspects, treatment and present a literature review related to this rare condition.
Keywords: Alacrima; Lacrimal gland; Lacrimal gland agenesis; Punctal plugs